PENGEMBANGAN APLIKASI WISATA KULINER LOKAL BERBASIS ANDROID MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Samuel Samuel; Agus Herwanto; Bambang Irawan; Budi Tjahjono (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
In the digital era, the regional tourism sector is required to continuously innovate in providing information and services to tourists, including promoting the potential of local culinary tourism. This research aims to design and develop an Android-based local culinary tourism application as an effort to support increased tourist visits to the region. The development method used is Rapid Application Development (RAD), which is considered capable of producing applications with a fast, flexible, and adaptive development process to user needs. The application provides a search feature for nearby culinary locations, recommendations for popular restaurants, travel route maps, and user reviews, supporting a more informative and interactive culinary tourism experience. Testing was conducted through several stages, from unit testing to system testing, to ensure each feature operates according to specifications. The development results indicate that this application can help tourists find culinary information practically while also supporting local culinary businesses in promoting their products digitally. It is hoped that this application can support increasing the attractiveness of culinary tourism in the region, strengthening the local tourism ecosystem, and making a significant contribution to the growth of the technology-based creative economy.